The spawning and development of Mopalia muscosa from fertilization through metamorphosis at Friday Harbor Laboratories - Nicholas, Khrista; Varney, Rebecca (My University, 2025)
Exploring unique physiological processes across animal taxa inspires ideas and innovations. Chitons are marine mollusks that biomineralize teeth with magnetite, an iron oxide mineral. Iron is toxic to animals in high concentrations, so past research focused on how adult chitons use iron. In situ spawning and fertilization of chitons have historically been unreliable, so larval and juvenile specimens have been difficult to obtain to study radula development. Here we describe methods that induced spawning in Mopalia muscosa and Katarina tunicata, as well as several methods that failed. We maintained cultures of M. muscosa through metamorphosis. Our experimental spawning trials and photographic documentation of M. muscosa build on past literature to further understand the embryology, development, and metamorphosis of chitons. In the future, the samples we collected across developmental stages will be used to reveal the timeline of morphological and transcriptomic changes of early stages of M. muscosa, especially as it relates to radula growth and the start of iron biomineralization.
Keywords: chiton; larval development; metamorphosis; Mopalia muscosa; Katarina tunicata